Comparative Metal Distribution in Hair of Pakistani and Libyan Population and Source Identification by Multivariate Analysis - Shah, Munir H.; Shaheen, N.; Khalique, A.; Alrabti, A. A. A.; Jaffar, M. (Environmental monitoring and assessment, 2006)
Using nitric acid-perchloric acid wet digestion based FAAS method ten selected metals (Cd, Co, Cr, Fe, K, Mn, Na, Ni, Pb and Zn) were determined in the scalp hair of male Pakistani and Libyan donors (n = 62), between 3-54 years age and residing in typical urban areas. The study was taken up to identify sources of metal distribution in two diverse population segments exposed to different environments. Sodium emerged with the highest mean hair concentration of 511.0 microg/g and 496.9 mug/g for Libyan and Pakistani donors respectively, followed by K, at 266.2 microg/g and 242.4 microg/g for the two donor categories. Cadmium showed the lowest mean hair concentration for both Pakistani (0.380 microg/g) and Libyan (0.530 microg/g) donors. Levels of Na, K, Pb, Cr and Cd were higher in hair of Libyan donors compared with Pakistani counterparts which showed higher comparative levels of Zn, Fe, Co, Ni and Mn. Strong metal-to-metal correlations were found between Na-K (r = 0.638) and Cd-Co (r = 0.574) for Pakistani donors, while for Libyan donors, Na-K (r = 0.680) and Fe-Mn (r = 0.624) correlations emerged as strongly significant. Only K was found to have a strong positive correlation (r = 0.611) with age for Pakistani donors while this correlation was significantly negative (r = -0.500) for Libyan donors, probably arising from individual food habits. Other metals showed no viable relationship with age. Principal Component Analysis (PCA) and Cluster Analysis (CA) of the data evidenced food, industrial emissions and automobile emissions as possible sources of metal distribution. The results of the present study are compared with those reported for subjects from other regions of the world.